A Chemist with a Strange Etiology of Rhabdomyolysis: A Case Report of a Rare Toxicological Emergency - Rajadurai Meenakshisundaram (eScholarship Publishing, University of California, 2021)
Introduction: Chloroform, a halogenated hydrocarbon, causes central nervous depression, hepatotoxicity, nephrotoxicity, and rhabdomyolysis. Historically, chloroform had been used as a general anaesthetic and today is still used in chemical industries. Lack of proper personal protective equipment and adequate knowledge about its toxic effects can lead to serious harm. Case report: A 33-year-old gentleman presented to the emergency department (ED) with altered mental status. Given his depressed mental status, the decision was made to intubate shortly after arrival for airway protection. Further history raised suspicion of occupational chloroform exposure. Brown-colored urine further strengthened suspicion of chloroform poisoning with resultant rhabdomyolysis. Forced alkaline diuresis and N-acetylcysteine were started in the ED. His mental status and respiratory efforts improved on hospital day two, and he was ultimately extubated. Creatine phosphokinase and myoglobin levels were initially high but gradually came down by hospital day six. On hospital day 10, the patient was deemed stable and safely discharged. Conclusion: A patient with chloroform inhalation who suffered resultant rhabdomyolysis and hepatotoxicity was successfully treated with early initiation of forced alkaline diuresis, N-acetylysteine, and hemodialysis.